1996
DOI: 10.1063/1.470905
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation process of size-selected aluminum cluster anions in collision with a silicon surface

Abstract: Dynamical processes involved in the collision of aluminum cluster anions, Al−N (4≤N≤25), with a silicon surface were investigated. Intact and fragment cluster anions, Al−n (n≤N), were produced upon the collision. The surf02ace-tangent and surface-normal recoil velocity components of these product a0n0ions were determined. The tangential recoil velocities of the fragment cluster anions were considerably slow, ranging from 5% to 30% of the velocity of the incident parent cluster anion, while the normal velocitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 26 publications
4
29
0
Order By: Relevance
“…2 The experimental study on the collision of (Ar) n against a graphite surface [13][14][15] has elucidated the dynamics of the energy and particle flows in the cluster-surface collision through the translational energy measurements of the fragments scattered from the surface. Similar information has been obtained in the collisional dissociation of (Al) 13 Ϫ against a silicon surface; the clusterimpact heating causes the cluster temperature to rise as high as 10 000 K. 16 We investigated energy redistribution in the impact of I 2 Ϫ ͑CO 2 ) n against a silicon surface through the measurements of the translational energy of its fragment anions. It was revealed that the surface-impact dissociation of I 2 Ϫ (CO 2 ) n proceeds via ͑1͒ preferential transmission of the collision energy to a particular vibrational mode such as the vibrational mode of I 2 Ϫ , and ͑2͒ rapid energy redistribution in the internal modes of the cluster anion and its neighboring surface atoms.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…2 The experimental study on the collision of (Ar) n against a graphite surface [13][14][15] has elucidated the dynamics of the energy and particle flows in the cluster-surface collision through the translational energy measurements of the fragments scattered from the surface. Similar information has been obtained in the collisional dissociation of (Al) 13 Ϫ against a silicon surface; the clusterimpact heating causes the cluster temperature to rise as high as 10 000 K. 16 We investigated energy redistribution in the impact of I 2 Ϫ ͑CO 2 ) n against a silicon surface through the measurements of the translational energy of its fragment anions. It was revealed that the surface-impact dissociation of I 2 Ϫ (CO 2 ) n proceeds via ͑1͒ preferential transmission of the collision energy to a particular vibrational mode such as the vibrational mode of I 2 Ϫ , and ͑2͒ rapid energy redistribution in the internal modes of the cluster anion and its neighboring surface atoms.…”
Section: Introductionmentioning
confidence: 71%
“…11,16,21 A supersonic expansion of CO 2 (1.5ϫ10 5 Pa) containing a͒ Author to whom correspondence should be addressed. I 2 ͑0.1-1 mol %͒ was bombarded by 350 eV electrons with an electron current of ϳ200 A.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fission of cluster ions into two fragments of about equal size was observed, together with evaporation, too. It was described for collisions of silicon anion clusters [22] and of certain metal anions and cations [23,24] at incident energies of tens of eV. Some alkali halide cluster ions were found to cleave to a series of two fragments of unequal size [25].…”
Section: Introductionmentioning
confidence: 99%